Postmodern epistemology and the Christian apologetics of CS Lewis - Wilson, D. N. (Verbum et ecclesia, 2006)
Evangelicalism at the turn of this century finds itself facing a challenge that undermines its very validity. This challenge is generally referred to as postmodernism. Within the contemporary evangelical paradigm, the context in which this term is generally used refers to epistemology - the structure and limitations of human self-consciousness. The gist of the popular post-modernist argument is that human consciousness always develops inductively - from the inside, outward - utilising a particular linguistic and cultural frame of reference in order to construct conceptions of reality. Human self-consciousness, as understood from this context, is therefore always ultimately, something that can only be referred to as insulated. In the light of this, human self- consciousness can have no direct access to what may be commonly referred to as, an absolute truth.